Doing a systematic review in health sciences - Cajala, Berta (Colegio Oficial de Psicólogos de Madrid, 2020)
This paper aims to provide a practical, summarized, and clear guide of steps to carry out a systematic review and is aimed at researchers in the field of Health Sciences. The review process runs from the initial questioning to the final report, providing useful information on tools available at each stage. Systematic review and meta-analysis are currently the evidence synthesis tools of the highest level of scientific quality. They are in themselves a secondary research methodology, whose objective is to locate, evaluate, and synthesize the best evidence by selecting original papers or quality primary publications. The procedure to achieve the objective is presented as a sequential and systematized process, in stages, following the transparency principle, so as to ensure its replicability.